One‐Pot and Shape‐Controlled Synthesis of Organic Cages - Zhao, Xiang; Liu, Yue; Zhang, Zhi‐Yuan; Wang, Yiliang; Jia, Xueshun; Li, Chunju (Angewandte Chemie International Edition, 2021)
Organic cages are fascinating because of their well‐defined 3D cavities, excellent stability, and accessible post‐modification. However, the synthesis is normally realized by fragment coupling approach in low yields. Herein, we report one‐pot, gram‐scale and shape‐controlled synthesis of two covalent organic cages (box‐shaped [4]cage and triangular prism‐shaped [2]cage) in yields of 46 % and 52 %, involving direct condensation of triangular 1,3,5‐tris(2,4‐dimethoxyphenyl)benzene monomer with paraformaldehyde and isobutyraldehyde, respectively. The cages can convert into high‐yielding per‐hydroxylated analogues. The [2]cage can be utilized as gas chromatographic stationary phase for high‐resolution separation of benzene/cyclohexane and toluene/methylcyclohexane. By changing the central moiety of the triangular monomer and/or aldehyde, this synthetic method would have the potential to be a general strategy to access diverse cages with tunable shape, size, and electronic properties. A one‐pot, gram‐scale and shape‐controlled synthesis of two covalent organic cages is presented. They can convert into high‐yielding per‐hydroxylated analogues that exhibit great potential for further modification. The [2]cage can be utilized as gas chromatographic stationary phase for high‐resolution separation of benzene/cyclohexane and toluene/methylcyclohexane.